Dividend policy and its implications on stock prices. Examples of evaluation in Indonesia - Meliana, Desy; Defung, Felisitas; Kusumawardani, Anisa (Technium Social Sciences Journal, 2021)
The food and beverage industry is one of the mainstay sectors that support the growth of manufacturing and the national economy in Indonesia. The more demand for products in the food and beverage industry, it will be very profitable for companies because of the large number of requests for these products, so that they are expected to get the maximum profit and attract investors to invest. With these logical considerations, we try to investigate the relationship between financial performance, ownership structure, macroeconomics, dividend policy, and stock prices in Indonesia. Data processing techniques are supported by path analysis, where secondary data is collected from IDX during the period 2013 to 2019. Path analysis classifies three structures to identify direct effects (structure one and structure two), then there is a triple structure based on indirect effects. From this study, it can be seen the interaction of the variables that have been limited to a model. As a result, there is a direct positive-significant relationship between financial performance and dividend policy, but ownership structure and macroeconomics actually have a negative effect, even though the probability of ownership structure is significant. On stock prices, dividend policy has given a signal that its effect has a significant positive impact. Particularly for the indirect effect, it illustrates if financial performance and ownership structure both affect stock prices through dividend policy positively and significantly. Because the relationship is quite systematic, the financial performance and ownership structure are considered successful, which is indicated by a positive path coefficient. On the other hand, in macroeconomics towards stock prices through dividend policy, the results are negative and insignificant.